FOLLOWING THE ACTION: How live bloggers are reimagining the professional ideology of sports journalism. (16th November 2016) - McEnnis, Simon
Abstract : Live sports blogging is a relatively new form of journalism in wide and frequent use by media companies but has received little attention from the academy. This article outlines a study that explored the belief and value system behind live sports blogging to establish whether shifts were taking place within the professional ideology of sports journalism. In-depth, semi-structured interviews were conducted with 10 live sports bloggers in the United Kingdom. The study found that live bloggers retained core journalistic values and beliefs of balancing objectivity and subjectivity, immediacy, providing a public service and editorial autonomy. However, live blogging's challenges of immediacy, interactivity and shifting consumption patterns have led to a reimagining of what these concepts mean and the skills and competences required. Live bloggers perceived their role as community builders and mediators of discussion as well as information providers, and this represents a new openness and inclusivity within the occupational base. Participants did not regard these changes to be a dumbing down of standards but rather a paradigm shift towards flattening hierarchies between journalist and audience. The findings suggest live bloggers have shown a greater willingness to adapt than previous research into the migration of sports journalists to digital platforms has found.